Diguanylate cyclase Dgc1 synthesizes c-di-GMP and modulates WL gum exopolysaccharide production in Sphingomonas sp. WG - Hui Li; Yanhui Jia; Hangxu Liu; Zaimei Zhang; Mengqi Chen; Huiyu Zheng; Mengqing Xu; Mengmeng Zang; Dong Wang; Yawei Sun; Hu Zhu; Jiqian Wang (Bioresource Technology, 2026)

High-coverage paleo-genome research identifies a pathogenic mutation on EXT1 in a Qing-period Chinese individual with multiple osteochondromas - Bangyan Wang; Haodong Chen; Fanhao Xi; Haoquan Bao; Hetong Wen; Panxin Du; Chenshuang Sun; Jianxue Xiong; Baoshuai Zhang; Xin Chang; Yawei Zhou; Chuan-Chao Wang; et al. (Molecular Genetics and Genomics, 2026)

Characteristics and mechanism of karst groundwater cycle evolution under large-scale exploitation: a case study of the Yanxi karst groundwater system - Yawei Feng; Fengxin Kang; Fengfeng Shi; Xuesen Wang; Xianzhou Meng; Yifu Fu; Aijun Li; Hao Chen; Qingcheng He (Carbonates and Evaporites, 2026)

Synergistic enhancement of microalgal fatty acids via Batch Bayesian Optimization-driven combinatorial additive engineering - Yu Zhao; Yawei Wu; Guopeng Chen; Shi Guo; Fangzhong Wang; Lei Chen; Weiwen Zhang; Jie Chen (Bioresource Technology, 2026)

Isolation and identification of tropical source Lactobacillus plantarum CK3 and its effects on fatty liver in laying hens - Yongzhen Chen; Xinyu Feng; Xinyi Zhang; Andrea Abreo Medina; Jiayu Feng; Xin Li; Meiyu Duan; Yawei Qiu; Fang Gan (Research in Veterinary Science, 2026)

Photocatalytic inhibition and mechanisms of adult Ulva prolifera by COF-supported CuS under visible light - Yingqi Zhang; Qingying Wei; Yun Tian; Yawei Zhang; Linqing Cui; Renjun Wang; Junfeng Chen (Journal of Environmental Chemical Engineering, 2026)

Decoding flood hazard responses to reticular river network changes using interpretable machine learning - Shanheng Huang; Peng Wang; Zulin Hua; Yueyang Dong; Rongxu Chen; Yawei Hu; Shimin Tian (Journal of Hydrology, 2026)

Seasonal shifts in dissolved organic matter composition drive the formation of nitrogenous disinfection byproducts via a carbon-nitrogen coupling mechanism in source water - Tianyu Chen; Shiyang Yu; Qiurui Zhang; Jing Qian; Yonghong Bi; Anen He; Lingxiangyu Li; Nanwen Zhu; Jitao Lv; Zhigang Li; Yawei Wang; Guibin Jiang (Environmental Research, 2026)

Light-triggered molecular lever in a MOF@COF nanosheet for synergistic enhancement of heat and mass transfer in CO2 photothermal desorption - Jingyu Bao; Mingjie Zhou; Zuxue Bai; Yawei Xie; Xuehui Jia; Jiajun Zeng; Yujie Huang; Ruimeng Wang; Jianmin Chen; Zhaowei Jia; Liqin Zhou; Zhongxing Zhao; et al. (Chemical Engineering Journal, 2026)

The meteorological and anthropogenic drivers of O3 and PM2.5 pollution in China's Ningbo based on WRF-CMAQ-ISAM - YuZhan Xie; Tijian Wang; Pulong Chen; Kuanguang Zhu; Tao Niu; Rong Li; Mengmeng Li; Hao Wu; Yawei Qu; Xu Liu; Congwu Huang (Atmospheric Pollution Research, 2026)

Experimental investigation of oxygen-enriched combustion in conjunction with plasma ignition and plasma-assisted combustion to improve ammonia combustion - Chen Wu; Qifu Lin; Dianwu Wu; Chengzhou Liu; Shilong Zhong; Hansheng Feng; Longwei Chen; Zhenyang Li; Yiman Jiang; Guangnan Luo; Yawei Song; Weiye Chen; et al. (Fuel, 2026)

N and S co-doped graphene-based single-atom catalysts for highly efficient nitrate reduction - Jin-Hang Liu; Yu Sun; Xiaoduo Jiang; Huixiong Jiang; Ruirui Wang; Yawei Wang; Huixian Ye; Xiudong Chen; Li-Ming Yang (Fuel, 2026)

A functional lactic acid bacteria strain that naturally produces hydroxytyrosol and its impact on the antioxidant activity and post-acidification of fermented milk - Panpan Han; Yangliu Liu; Min Zhang; Yinglin Chen; Simiao Zhai; Zhixin Wang; Yawei Ning; Yingmin Jia (Food Bioscience, 2026)

A portable source-informed machine learning framework for predicting heavy metals in legacy smelting sites with strong spatial heterogeneity - Xu Cao; Yan Liang; Yawei Zhao; Tianhuan Chen; He Huang; Tian Xie (Journal of Hazardous Materials, 2026)

A computational screening study of Dual-Metal M1M2@1T-MoS2 with various coordination environments as catalysts for the hydrogen evolution reaction - Tingting Li; Guohao Yin; Haiyan Zhu; Shanlin Chen; Chou Wu; Shaobo Jia; Ghulam Meeladi; Yawei Li; Yixuan Huang (Fuel, 2026)

Revealing the protein dynamics of low-temperature Daqu during Daqu-making process by metaproteomics, enzyme activity assay, and ELISA - Shuai Zhao; Yunfei Xia; Xing Chen; Yan Chen; Xuezhuang He; Menqing Cui; Yuchen Gao; Lei Wang; Jing Lu; Yawei Shi (Food Bioscience, 2026)

Exposure to multiple metals, maternal glucose homeostasis and gestational diabetes mellitus: A prospective cohort study - Hui Guo; Sijia Liu; Wenjing Li; Yongliang Feng; Ping Zhang; Changqing Li; Shuqing Bai; Yuanyuan Yang; Xi Chen; Suping Wang; Yawei Zhang; Zhijun Meng; et al. (Environmental Research, 2026)

A proton-relay strategy with K-modulated N/P proton pairs over Ru-based catalysts for efficient ammonia decomposition - Shuyu Chen; Rui Chen; Liang Wang; Haibo Tang; Rui Wang; Tian Tian; Yawei Zhou; Zihan Meng; Haolin Tang (Chemical Engineering Journal, 2026)

Bisphenol A promotes esophageal carcinogenesis by activating the MMP1–PCOLCE regulatory axis and remodeling the tumor immune microenvironment - Yawei Cui; Guohang Shen; Huiling Chen; Ruoyan Wang; Chengping Zhang; Lu Han; Kaiyong Wang; Yang Chen; Junfeng Li; Xia Gao; Yupei Dai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Integrated Heart Rate Monitoring and Transcriptomic Analyses Reveal Distinct Responses to Hypo- and Hypersalinity Stress in Abalone - Nan Chen; Run Hu; Yun Chen; Weiwei You; Caihuan Ke; Yawei Shen (Fishes, 2026)
In the context of global climate change, intensified salinity fluctuations driven by altered precipitation, extreme rainfall events, and typhoons have emerged as a major threat to coastal mollusk aquaculture. In this study, integrated physiological and transcriptomic analyses were performed to investigate the responses of Pacific abalone (DD, Haliotis discus hannai) and its hybrid (DF, H. discus hannai ♀ × H. fulgens ♂) to hypo- and hypersalinity stress. Two salinity breakpoints (BPS1 for hyposalinity, BPS2 for hypersalinity) were identified using heart rate monitoring to indicate the osmotic tolerance thresholds of the abalone. The BPS1 and BPS2 values did not differ significantly between the DD and DF groups. However, a subsequent 30-day culture trial confirmed that exposure to the salinity level corresponding to BPS1 significantly reduced growth and survival of both DD and DF groups. To explore the molecular mechanisms underlying these two salinity breakpoints in abalone, the transcriptomes of hemocytes and gill tissues were profiled under both stress conditions. Both hypo- and hypersalinity stress induced pronounced transcriptomic responses in abalone, accompanied by upregulated differentially expressed genes (DEGs) significantly enriched in pathways like TNF and NF-κB signaling, including genes like piap, diap2, birc7-a, birc2, and birc3. However, abalone exhibited more intense responses to hypersalinity stress, as reflected by a greater number of annotated differentially expressed genes (DEGs) and more complex transcriptional regulation. Overall, this study integrates physiological assessment based on heart rate monitoring, aquaculture trials, and transcriptomic analysis to advance our mechanistic understanding of osmotic stress adaptation in abalone, while laying a scientific foundation for the sustainable development of abalone aquaculture under global climate change.

Sustainable lithium extraction from low-grade aqueous resources via reverse Li/Mg separation enabled by hydrated cation-π interaction - Huixiong Jiang; Xing Liu; Jin-Hang Liu; Xiudong Chen; Ruirui Wang; Yawei Wang; Changchao Zhan; Xiaohua Cao; Xiushen Ye; Guosheng Shi (Journal of Cleaner Production, 2026)

Understanding the differences in ignition and combustion characteristics between raw coal and pyrolyzed char: A combined PLIF measurement and DFT calculation - Yawei Song; Sheng Su; Qifu Lin; Longwei Chen; Chengzhou Liu; Weiye Chen; Zhenyang Li; Yiman Jiang; Dianwu Wu; Hansheng Feng; Guangnan Luo; Jun Xiang (Fuel, 2026)

A methodical comparative analysis of the improved dechlorination of trichloroethylene (TCE) using C-, N-, and S-modified zero-valent iron (ZVI) - Xiang Luo; Hongwei Chen; Hongjian Shen; Ling Zhang; Jinbo Chen; Shuai Liu; Bo Gao; Honglei Zhang; Yawei Gu (Journal of Water Process Engineering, 2026)

Microdroplet induced catalyst surface fields boost hydroxyl radical generation and its application - Ange Zhu; Jingkang Gao; Yunjun Mei; Mengxi Cao; Fengjie Chen; Bolei Chen; Yong Liang; Yawei Wang (Journal of Hazardous Materials, 2026)

Enhanced simultaneous removal of TCE and Cr(VI) by nitrided nano zero-valent iron (FexN@nZVI): Performance and mechanisms - Ling Zhang; Guangfei Gao; Fengxu Shang; Xinze Song; Zhenjie Li; Lei Chen; Junjie Zhang; Wenyu Wang; Xiaoguo Shi; Bo Gao; Yawei Gu; Xuan Zhang (Journal of Environmental Chemical Engineering, 2026)

Risk factors for antibiotic resistance and 30-day mortality among adult patients with acute leukemia and Escherichia coli bloodstream infection - Juan Wu; Wei Wang; Kaili Du; Zhongxian Liao; Yawei Shi; Munire Abudumaijiti; Jilai Liu; Jiadi Chen; Xinmiao Fu (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Hysteretic behavior of reinforced ultra-high-performance concrete columns under combined axial and flexural loads - Qiwu Wang; Zhi Fang; Wenjie Zheng; Fei Peng; Yawei Fang; Jiaxing Chen; Hua Huang (Bulletin of Earthquake Engineering, 2026)

Activation of peroxydisulfate with N-doped CoFe2O4 for tetracycline hydrochloride degradation: the predominant role of radical and singlet oxygen cooperation - Jiawei Wei; Xia Chen; Yawei Gu; Wenqiang Jiang (Journal of Water Process Engineering, 2026)

Expansion of the rhizosphere soil and phyllosphere bacterial resistomes following repeated farmland application of high-temperature granulation-treated antibiotic fermentation residues - Ruiqi Wan; Tianyu Chen; Yanping Xun; Yazhuo Chen; Jitao Lv; Lingyi Meng; Kristian Koefoed Brandt; Yawei Wang (Journal of Environmental Sciences, 2026)

Short-term effect of changing water regimes on the soil nematode community in rice-duckweed system under water-saving irrigation - Zeeshan Ahmed; Junzeng Xu; Weixuan Liu; Xiaoyin Liu; Yawei Li; Hang Guo; Shengyu Chen (European Journal of Soil Biology, 2026)

Applications of machine learning-based quantitative structure activity relationship (ML-QSAR) models in environmental science - Chao Chen; Yujia Tan; Yawei Liu; Miaomiao Sun; Zhiquan Wang; Xiangyong Zheng; Zhemin Shen; Min Zhao (Environmental Research, 2026)

Nutrient recovery from source-separated urine and urease inhibition during evaporation by a combination of salt, absorbent material, and dehumidification - Weikun Chen; Huijun Xiang; Chun Chen; Lanyue Feng; Ke Bei; Yawei Liu; Min Zhao; Xiangyong Zheng (Chemical Engineering Journal, 2026)

Nanopolystyrene and chrysene-induced gill damage in fish - Rahma Sakina Said Aly; Yawei Shen; Jinliang Zhao; Tiantian Chen; Xiaowu Chen (Aquaculture, 2026)

Novel enhanced network integrating transformations of DOM and microorganisms (ENITM) elucidates microbial-driven transformation pathways in estuarine sediments - Shiyang Yu; Jitao Lv; Xindong Ma; Lu Jiang; Qiurui Zhang; Tianyu Chen; Han Fang; Dong Cao; Lixia Zhao; Yawei Wang (Water Research, 2026)

Corrigendum to “Genomic and functional characterization of the lect2 gene from Siniperca chuatsi” [Fish Shellfish Immunology 107 (2020) 146–155] - Yawei Shen; Ming Cao; Shoujie Tang; Yan Zhao; Jinliang Zhao; Xiaowu Chen; Yanhui Bi (Fish & Shellfish Immunology, 2026)

Invertible neural network for real-time inversion and uncertainty quantification of ultra-deep resistivity measurements - George Bittar; Sihong Wu; Yawei Su; Shubin Zeng; Jiajia Sun; Xuqing Wu; Yueqin Huang; Jiefu Chen (Computers & Geosciences, 2026)

An exergy-guided thermodynamic framework for the optimization of electro-membrane-based coupled process - Ruochen Shen; Yawei Du; Lurong Wang; Mengmeng Sun; Tianyi Chen; Shizhao Wang; Jingtao Bi; Wenhao Li; Jianlu Liu; Yingying Zhao (Water Research, 2026)

Spatial distribution and ecological risk assessment of pharmaceuticals and personal care products across China's coastal waters - Jia Shao; Tianyu Chen; Lu Jiang; Jitao Lv; Jingyu Zhang; Dan Wu; Fenfen Zhang; Yawei Wang; Guibin Jiang (Journal of Hazardous Materials, 2026)

Morphological and functional analysis of saccus vasculosus of mandarin fish ( Siniperca chuatsi ) - Rahma Sakina Said Aly; Jiajie Fang; Keying Li; Xiao Ma; Jiong Gao; Meng Zhang; Xiaowu Chen; Yawei Shen (Journal of Fish Biology, 2026)
The saccus vasculosus (SV) is a specialized periventricular organ found in some species of teleost and elasmobranch fishes, located at the back of the hypothalamus and pituitary gland. However, its function remains incompletely understood. In this study, histological, transmission electron microscopy (TEM) and transcriptomic analyses were employed to investigate the SV of the mandarin fish ( Siniperca chuatsi ) to gain insights into its morphology, gene expression profile and function. Through histological staining techniques, different cell types within the SV can be identified and characterized. The SV is highly folded vascularized neuroepithelium and is deeply connected to blood vessels. TEM studies showed that the capillaries that produced the lumen formed complex narrow channels are linked to the third ventricle of the hypothalamus. The bright neuroepithelium is formed by coronet cells and supporting glial cells, interspersed with liquor‐containing neurons, while the dark contrast is attributed to the presence of heavy elements such as calcium. We identified 28 specific genes in SV, which are most enriched in the purine metabolism pathway, including the genes of pde9al , pde9ac , pde6hl and sgc88el . Gene Ontology biological process analysis for the SV‐specific genes showed that response to osmotic stress was the hub term according to the enrichment maps. Additionally, SV‐specific genes opsin ( opsin8b ), photoreceptor ( pcare1 ) and aquaporin ( aqp4 , aqp9l ) of Siniperca chuatsi may indicate that they play a role as a sensor of season and are involved in osmoregulation. This study, the first on the Siniperca chuatsi , suggests that the SV may have unique physiological functions in teleost fish.

Supercritical water-assisted acid leaching for efficient copper recovery from waste circuit boards: Mechanisms, optimization, and sustainable metal extraction - Siyi Kang; Yawei Yang; Jingwei Chen; Jiaqiang E (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Self-regulated mineralization of CO2 capture products from functionalized ionic liquid into disc-shaped vaterite” [Chem. Eng. J. 522 (2025) 167956] - Yang Chen; Jingyi He; Yawei Zeng; Shaoyun He; Zhen He; Hui Hu (Chemical Engineering Journal, 2025)

Lactobacillus rhamnosus GG-derived extracellular vesicles improve cholestatic liver injury by regulating the gut microbiota and bile acid metabolism - Zhongyu Wang; Yubo Wang; Yawei Qiu; Andrea Del Pilar Abreo Medina; Yongwang Liu; Mengdie Shi; Jinyan Li; Yanyan Wang; Xianjiao Liu; Xingxiang Chen; Kehe Huang; Yunhuan Liu (Chemical Engineering Journal, 2025)

Microbial-mediated transformation shapes the molecular diversity of landfill leachate under anthropogenic and natural covariation - Qiurui Zhang; Jitao Lv; Shiyang Yu; Tianyu Chen; Yue Sun; Feifei Li; Lu Bai; Xianwei Wang; Xiaosong He; Yong Nie; Nanwen Zhu; Yawei Wang; et al. (Water Research, 2025)

Transcriptome to reveal the immunological defenses in mandarin fish (Siniperca chuatsi) skin with LPS and poly (I:C) infection - Yawei Shen; Jiong Gao; Meng Zhang; Yongjing Li; Rahma Sakina Said Aly; Lei Wang; Miao Yu; Hongxia Jiang; Zhigang Qiao; Xiaowu Chen (Fish & Shellfish Immunology, 2025)

Removal of insoluble barium scales from reverse osmosis membranes by grafting molecular springs - Xin Wen; Yuyan Hai; Rui Ma; Xu Liang; Yawei Duan; Jingyun Chen; Hui Wei; Rihua Xiong (Desalination, 2025)

Enhanced CO2 electrolysis via H2/CH4 assistance in a symmetric solid oxide electrolysis cell with an alloy-perovskite composite electrode - Shuangzhen Li; Feiya He; Jing Yan; Yawei Li; Si-Dian Li; Huili Chen (Chemical Engineering Journal, 2025)

Study on the NO2 pollution and its connection with PM2.5 and O3 in Dazhou based on source apportionment - Xu Liu; Pulong Chen; Congwu Huang; Tijian Wang; Tao Niu; Mengmeng Li; Rong Li; Hao Wu; Yawei Qu (Atmospheric Pollution Research, 2025)

The effect of fluid saturation on the elastic properties of coal measure rocks under confining pressure - Fei Gong; Guangui Zou; Suping Peng; Zhaoji Zhang; Hao Chen; Yawei Zhao (Journal of Applied Geophysics, 2025)

Self-regulated mineralization of CO2 capture products from functionalized ionic liquid into disc-shaped vaterite - Yang Chen; Jingyi He; Yawei Zeng; Shaoyun He; Zhen He; Hui Hu (Chemical Engineering Journal, 2025)

Local collaboration between oxygen vacancy, palladium and platinum trimer triggers exceptional performance in the alkaline fuel cell - Dinesh Bhalothia; Che Yan; Yawei Wu; Jui-Cheng Kao; Yu-Chieh Lo; Haolin Li; Nozomu Hiraoka; Hirofumi Ishii; Yen-Fa Liao; Sheng Dai; Chen-Hao Wang; Alice Hu; et al. (Chemical Engineering Journal, 2025)

Seismic response and failure mode of a subway station in a ground fissure area - Xuan Chen; Yawei Wu; Hongquan Teng; Zhongming Xiong; Qiren Sun; Yan Zhuge (Earthquake Engineering and Engineering Vibration, 2025)

Stem nematode disease resistance-conferring gene identification in sweet potato using combined BSA-Seq and BSR-Seq analyses - Shouchen Qiao; Jingwei Chen; Yawei Li; Yannan Wang; Jukui Ma; Zhihe Kang; Qianqian Bian; Guozheng Cao; Guorui Zhao; Guohong Yang; Yanping Fan; Houjun Sun; et al. (Planta, 2025)

Excellent lithium storage performance of SnOx/Ti3C2 with low Sn content by controlling the oxygen vacancy content - Tingting Xu; Yawei Li; Jinghan Zhang; Haixiang Huang; Bogu Liu; Xiaohong Chen; Hong Zeng; Ying Wu (Chemical Engineering Journal, 2025)

Methanol-driven advanced reduction of nitrate and 2,4,6-tribromophenol by UV-activated photolysis - Yawei Xie; Yue Wang; Shijie Wu; Hmuu Khet Nwe Zaw; Yaozu Jin; Shiyi Ni; Lyujun Chen; Hongyuan Liu (Process Safety and Environmental Protection, 2025)

Improved degradable, mechanical, and osteoimmunity-regulating performances of additively manufactured Zn-Mg alloy with heterogeneous microstructure for augmented bone regeneration - Zhengjun Lin; Luxin Liang; Yawei Li; Yanlin Wu; Jing Li; Bing Wang; Chao Chen; Tang Liu (Chemical Engineering Journal, 2025)

Gram-scale synthesis of unsupported Pt-rare earth nanosponge for enhanced stability in proton exchange membrane fuel cells - Chenhao Li; Hao Wang; Fangren Qian; Yawei Li; Qinqin Sang; Qingjun Chen; Jialiang Liao; Yihan Zhu; Yanrong Liu; Suojiang Zhang (Chemical Engineering Journal, 2025)

Seasonal variation in two culture systems and genome-wide association analysis of taurine content in the foot muscles of the Pacific abalone (Haliotis discus hannai) - Ziheng Yin; Junyu Liu; Wenchao Yu; Yawei Shen; Yang Gan; Yexin Chen; Jinwei Ke; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2025)

Sufficient burial depth is a prerequisite for Chinese cyclina (Cyclina sinensis) to maintain normal life activities - Yurou Ma; Shiyu Yan; Zhengyu Shao; Guolong Zhou; Ang Hu; Yawei Bu; Huimin Wang; Xinqi Lv; Jianyu Liu; Yihua Chen; Zhiguo Dong (Aquaculture, 2025)

Anti-inflammatory effect of food bioactives in inflammatory bowel disease: Role of the gut microbiome - Yawei Zhang; Lufan Zhang; Yang Dong; Yunwei Yang; Mengxing Li; Qian Chen; Dan Wang; Yuzheng Wu; Tao Wang (Food Bioscience, 2025)

Optimizing straw strip-mulching to enhance winter wheat productivity in semi-arid drylands - Rui Li; Yuzhang Chen; Yuwei Chai; Yawei Li; Jiantao Ma; Hongbo Cheng; Lei Chang; Shouxi Chai (Field Crops Research, 2025)

Soil pH modulates the impact of ammonia-based fertilizers on N-cycling microbial genes in terrestrial ecosystems - Xue Zhou; Yiyun Chen; Yawei Li (European Journal of Soil Biology, 2025)

Increased spike density and enhanced vegetative growth as primary contributors to improvement of dryland wheat yield via surface mulching - Yuwei Chai; Yawei Li; Rui Li; Lei Chang; Hongbo Cheng; Jiantao Ma; Yuqing Qin; Fanxiang Han; Changgang Yang; Yuzhang Chen; Qian Chen; Yao Zhang; et al. (Field Crops Research, 2025)

A Comprehensive Review of Ship Automatic Rudder Technology: Development, Challenges, and Prospects - Minjie Zheng; Qianqiang Chen; Daowei Yan; Yawei Zhang (Journal of Marine Science and Engineering, 2025)
Ship automatic rudder systems are critical to enhancing the precision, safety, and intelligence of modern navigation, which plays a significant role in optimizing vessel control, reducing crew workload, and improving operational efficiency. First, this paper undertakes a meticulous analysis of the evolution of automatic rudder technology research through the application of bibliometric analytical methodologies. Second, a thorough literature review is conducted, focusing on the fundamental components of automatic rudder technology, encompassing sensor technologies, control algorithms, and basic functionalities, including both the latest advancements and the distinct traits of various technological approaches and algorithms. Third, the core functions of automatic rudder technology are analyzed, which includes heading control, wave compensation, ship collision avoidance, safety control mechanisms, path planning, and tracking control. Lastly, this paper summarizes the principal challenges encountered during the development of automatic rudder technology and proposes potential directions for future advancements.

Genome-wide association study reveals growth-related mutations and candidate genes at early growth stages in largemouth bass (Micropterus salmoides) - Xiao Ma; Dongcai Chen; Zhilin Jia; Yue Xu; Zhigang Qiao; Lei Wang; Hongxia Jiang; Miao Yu; Yongjing Li; Xiaotian Gao; Chunlong Zhao; Yawei Shen; et al. (Aquaculture, 2025)

Co-incorporation of C and S into zero-valent iron to enhance trichloroethylene dechlorination: Kinetics, electron efficiency, and dechlorination capacity - Xuan Zhang; Siyu Xu; Yawei Gu; Ling Zhang; Longquan Zhang; Fengxu Shang; Xinze Song; Zhen Wang; Xiaoguo Shi; Honglei Zhang; Runze Bi; Jinbo Chen (Journal of Environmental Chemical Engineering, 2025)

Mechanism investigation into static magnetic field effects on enhancing surfactin productivity by Bacillus subtilis - Yamei Jin; Sirui Chen; Qiyan Zhao; Na Yang; Yawei Ning; Xueming Xu (Food Bioscience, 2025)

Advances in regional-scale crop growth and associated process modeling - Wenfeng Liu; Yawei Bai; Taisheng Du; Mengxue Li; Hong Yang; Shichao Chen; Chuanbin Liang; Shaozhong Kang (Science China Earth Sciences, 2025)

Ancient genomes shed light on the long-term genetic stability in the Central Plain of China - Hao Ma; Yawei Zhou; Rui Wang; Fei Yan; Haodong Chen; Limin Qiu; Jing Zhao; Li Jin; Chuan-Chao Wang (Science Bulletin, 2025)

Genome-wide association analysis study on host resistance against the Aeromonas veronii of largemouth bass Micropterus salmoides - Meng Zhang; Xiao Ma; Zerui Wang; Yuqing Han; Zhilin Jia; Dongcai Chen; Yue Xu; Zhigang Qiao; Xinyu Jiang; Lei Wang; Hongxia Jiang; Miao Yu; et al. (Fish & Shellfish Immunology, 2025)

Negative emotional eating patterns in Chinese adolescents: A replication and longitudinal extension with latent profile and transition analyses - Hongbin Weng; Wesley R. Barnhart; Hana F. Zickgraf; Urvashi Dixit; Yawei Cheng; Gui Chen; Jinbo He (Appetite, 2025)

The weak association between hypoxia tolerance and thermal tolerance increases the susceptibility of abalone to climate change - Yawei Shen; Yue Dai; Feng Yu; Wenzhu Peng; Junyu Liu; Weiwei You; Xuan Luo; Caihuan Ke; Nan Chen (Environmental Research, 2025)

Ultrasensitive and high selectivity detection of fibrin using Y-shaped DNA-homing peptide doped probe on localized surface plasmon resonance platform - Yawei Chen; Yuanfu Zhang; Xue Zhao; Wenyu Xu; Shuhao Wang (Analytica Chimica Acta, 2025)

Heat stress induces a three-phase thermoregulatory response in different hot and humid environments in rats - Lei Li; Jikuai Chen; Juelin Chen; Yawei Wang; Yankun Pei; Man Wang; Wenjun Chang; Jun Ma; Qing Song; Shuogui Xu (Science of The Total Environment, 2024)

Versatile plant genome engineering using anti-CRISPR-Cas12a systems - Yao He; Shishi Liu; Long Chen; Dongkai Pu; Zhaohui Zhong; Tang Xu; Qiurong Ren; Chuan Dong; Yawei Wang; Danning Wang; Xuelian Zheng; Fengbiao Guo; et al. (Science China Life Sciences, 2024)

Optimized multi-point hemispherical grid model with adaptive grid division based on the prior information of multipath error - Xuan Zou; Yawei Wang; Zhiwen Wu; Weiming Tang; Chen Zhou; Zhiyuan Li; Chenlong Deng; Yangyang Li; Yongfeng Zhang (Advances in Space Research, 2024)

Construction method and case study of digital twin system for combine harvester - Yanxin Yin; Bowen Ma; Zhijun Meng; Liping Chen; Mengnan Liu; Yawei Zhang; Bin Zhang; Changkai Wen (Computers and Electronics in Agriculture, 2024)

Comprehensive characterization of the differences in metabolites, lipids, and volatile flavor compounds between Ningxiang and Berkshire pigs using multi-omics techniques - Qian Wang; Hu Gao; Yawei Fu; Yue Chen; Gang Song; Zhao Jin; Yuebo Zhang; Jie Yin; Yulong Yin; Kang Xu (Food Chemistry, 2024)

Optimal conditions for cryopreservation by vitrification of largemouth bass (Micropterus salmoides) embryos - Meng Zhang; Xiao Ma; Yuqing Han; Zerui Wang; Zhilin Jia; Dongcai Chen; Zhigang Qiao; Xiaotian Gao; Chunlong Zhao; Yawei Shen (Animal Reproduction Science, 2024)

Characteristics of disinfection byproducts from dissolved organic matter during chlor(am)ination of source water in Tibetan Plateau, China - Ruiqing Chen; Tianyu Chen; Yukun Zhou; Linfeng Li; Lingxiangyu Li; Nali Zhu; Zhigang Li; Yawei Wang; Guibin Jiang (Science of The Total Environment, 2024)

Experimental study on navigation performance of bionic underwater vehicle inspired by sea turtle - Hao Ding; Qiang Gao; Yawei Zhu; Haipeng Shi; Kai Chen; Ruoqian Chen (Ocean Engineering, 2024)

Short time-series expression transcriptome data reveal the gene expression patterns and potential biomarkers of blood infection with LPS and poly (I:C) in Mandarin fish (Siniperca chuatsi) - Yawei Shen; Rahma Sakina Said Aly; Tiantian Chen; Hewei Jiang; Yufei Liu; Yongxiang Wang; Xiaowu Chen (Fish & Shellfish Immunology, 2024)

Synergistic effect of Bi and Fe for suppressing hydrogen evolution reaction (HER) and enhancing electrochemical nitrogen reduction reaction (eNRR) performance - Wenhua Guo; Yawei Li; Si-dian Li; Zongping Shao; Huili Chen (Chemical Engineering Journal, 2024)

Orbital-paced Oceanic Anoxic Event 2 evolution and astrochronology in the Mentelle Basin (Australia) at southern high latitudes - Kang Xu; Yi Zhong; H. Tsikos; Hongjin Chen; Yawei Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

A review of the pollution signatures of polycyclic aromatic hydrocarbons in the sediments of the East China Sea - Fang Yin; Chen Gao; Daolun Feng; Yawei Sun (Environmental Pollution, 2024)

Thyroid disrupting effects and the developmental toxicity of hexafluoropropylene oxide oligomer acids in zebrafish during early development - Xiaohui Zhao; Xianghan Meng; Dan Yang; Shasha Dong; Jianhui Xu; Dezhi Chen; Yawei Shi; Ya Sun; Guanghui Ding (Chemosphere, 2024)

Investigating functional mechanisms in the Co-biodegradation of lignite and guar gum under the influence of salinity - Bing Li; Hongyu Guo; Ze Deng; Linyong Chen; Changjiang Ji; Xiaokai Xu; Yawei Zhang; Song Cheng; Zhenzhi Wang (Journal of Environmental Management, 2024)

Low-permittivity BaCuSi4O10-based dielectric Ceramics: An available solution to connect low temperature cofired ceramic technology and millimeter-wave communications - Wei Wang; Xin Wang; Jian Bao; Jiapei Jiang; Zhen Fang; Biaobing Jin; Zhongqi Shi; Moustafa Adel Darwish; Yawei Chen; Qixin Liang; Meirong Zhang; Diming Xu; et al. (Chemical Engineering Journal, 2024)

Enhanced Fenton performance of wet-mechanochemically synthesized FeS2/Biochar: The multiple synergistic effect derived from mutual element doping - Zunqing Wen; Xiaoguo Shi; Yawei Gu; Ke Ma; Xiaozhe Song; Ao He; Chen Wang; Nianbo Zhang; Huiying Sui; Chongqing Xu; Rong Xue (Chemical Engineering Journal, 2024)

Assessment major NOx sources to nitrate of TSP around the Danjiangkou reservoir using isotopes and a Bayesian isotope mixing model - Chunyan Xiao; Yimeng Sun; Tongqian Zhao; Guizhen Wang; Pengbo Li; Yawei Zhao; Feihong Chen (Atmospheric Pollution Research, 2024)

Long‒term trends in surface thermal environment and its potential drivers along the urban development gradients in rapidly urbanizing regions of China - Chengyu Zhao; Hongkai Zhu; Shuyi Zhang; Ziwen Jin; Yiwen Zhang; Yawei Wang; Yadie Shi; Jianhui Jiang; Xiaoyong Chen; Min Liu (Sustainable Cities and Society, 2024)

Experimental study on the dynamic responses of harbour seal whiskers in the wake of caudal fin - Hanghao Zhao; Zhimeng Zhang; Weilin Chen; Yawei Zhao; Edward Yaw Sefah; Chunning Ji; Dekui Yuan (Ocean Engineering, 2024)

Experimental study on flow-induced vibrations of an equilateral triangular prism with a high mass ratio - Yawei Zhao; Zhimeng Zhang; Chunning Ji; Hanghao Zhao; Weilin Chen (Ocean Engineering, 2024)

Associations of environmental cadmium exposure with kidney damage: Exploring mediating DNA methylation sites in Chinese adults - Yuan Wei; Xiaochen Wang; Qi Sun; Wanying Shi; Wenli Zhang; Xu Gao; Yawei Li; Ruiting Hao; Xiaojie Dong; Chen Chen; Kangning Cao; Weilong Jiang; et al. (Environmental Research, 2024)

Characteristics of advanced anaerobic digestion sludge-based biochar and its application for sewage sludge conditioning - Qian Chen; Xingmin Fu; Jiawei Wang; Yawei Zhao; Wei Wang; Abdul Ghaffar Memon; Huihui Zhang; Yang Wen (Bioresource Technology, 2024)

Domestication affects nitrogen use efficiency in foxtail millet - Yufeng Deng; Yawei Chen; Taiji Kou; Yukun Bo; Meicheng Zhao; Feng Zhu (Euphytica, 2024)

The silent threat: Nanopolystyrene and chrysene pollutants disrupt the intestinal mucosal barrier, new insights from juvenile Siniperca chuatsi - Tiantian Chen; Rahma Sakina Said Aly; Yawei Shen; Shoujie Tang; Yan Zhao; Jinliang Zhao; Xiaowu Chen (Science of The Total Environment, 2024)

Reducing oil absorption in pea starch through two-step annealing with varying temperatures - Shumin Xie; Zihan Li; Qingfei Duan; Weijuan Huang; Wei Huang; Yawei Deng; Pei Chen; Fengwei Xie (Food Hydrocolloids, 2024)

TREM2 Deficiency Aggravates NLRP3 Inflammasome Activation and Pyroptosis in MPTP-Induced Parkinson’s Disease Mice and LPS-Induced BV2 Cells - Peiting Huang; Zhanyu Zhang; Piao Zhang; Jiezhu Feng; Jianwei Xie; Yinjuan Zheng; Xiaomei Liang; Baoyu Zhu; Zhenzhen Chen; Shujun Feng; Lijuan Wang; Jiahong Lu; et al. (Molecular Neurobiology, 2024)
Microglia-mediated neuroinflammation plays a crucial role in the pathogenesis of Parkinson’s disease (PD). Triggering receptor expressed on myeloid cells 2 (TREM2) confers strong neuroprotective effects in PD by regulating the phenotype of microglia. Recent studies suggest that TREM2 regulates high glucose-induced microglial inflammation through the NLRP3 signaling pathway. This study aimed to investigate the effect of TREM2 on NLRP3 inflammasome activation and neuroinflammation in PD. Mice were injected with AAV-TREM2-shRNA into both sides of the substantia nigra using a stereotactic injection method, followed by intraperitoneal injection of MPTP to establish chronic PD mouse model. Behavioral assessments including the pole test and rotarod test were conducted to evaluate the effects of TREM2 deficiency on MPTP-induced motor dysfunction. Immunohistochemistry of TREM2 and tyrosine hydroxylase (TH), immunohistochemistry and immunofluorescence Iba1, Western blot of NLRP3 inflammasome and its downstream inflammatory factors IL-1β and IL-18, and the key pyroptosis factors GSDMD and GSDMD-N were performed to explore the effect of TREM2 on NLRP3 inflammasome and neuroinflammation. In an in vitro experiment, lentivirus was used to interfere with the expression of TREM2 in BV2 microglia, and then lipopolysaccharide (LPS) and adenopterin nucleoside triphosphate (ATP) were used to stimulate inflammation to construct a cellular inflammation model. The expression differences of NLRP3 inflammasome and its components were detected by qPCR and Western blot. In vivo, TREM2 knockdown aggravated the loss of dopaminergic neuron and the decline of motor function. After TREM2 knockdown, the number of activated microglia was significantly increased, and the expression of cleaved caspase-1, NLRP3 inflammasome, IL-1β, GSDMD, and GSDMD-N was increased. In vitro, TREM2 knockdown aggravated the inflammatory response of BV2 cells stimulated by LPS and promoted the activation of NLRP3 inflammasome through the NF-κB pathway. In addition, TREM2 knockdown also promoted the expression of TLR4/MyD88, an upstream factor of the NF-κB pathway. Our vivo and vitro data showed that TREM2 knockdown promoted NLRP3 inflammasome activation and downstream inflammatory response, promoted pyroptosis, and aggravated dopaminergic neuron loss. TREM2 acts as an anti-inflammatory in PD through the TLR4/MyD88/NF-κB pathway, which extends previous findings and supports the notion that TREM2 ameliorates neuroinflammation in PD.

Nanoplastics and chrysene pollution: Potential new triggers for nonalcoholic fatty liver disease and hepatitis, insights from juvenile Siniperca chuatsi - Tiantian Chen; Hewei Jiang; Yaoji He; Yawei Shen; Zequn Huang; Yifeng Gu; Qun Wei; Jinliang Zhao; Xiaowu Chen (Science of The Total Environment, 2024)

Enhanced fluid mixing using a novel multi-stage static pipeline mixer: Numerical simulation and mechanism analysis - Jiaheng Zhao; Xing Li; Zedong Lu; Wenjun Chi; Zhibin Wang; Yawei Chen (Journal of Water Process Engineering, 2024)

Biological effects of perfluoroalkyl substances on running water ecosystems: A case study in Beiluo River, China - Xi Li; Qiang Wang; Qi Li; Yawei Wang; Yulu Tian; Anen He; Yan Chen; Shaocheng Si (Journal of Hazardous Materials, 2024)

Sustainability evaluation of urban large-scale infrastructure construction based on dynamic fuzzy cognitive map - Hongyu Chen; Shidong Cheng; Yawei Qin; Wen Xu; Yang Liu (Journal of Cleaner Production, 2024)

Criticality assessment of minerals associated with China's battery technologies - Yawei Huang; Peng Wang; Yao Wang; Heming Wang; Yue Zhang; Xiaozhu Xu; Chao Wang; Qiang Yue; Tao Du; Wei-Qiang Chen (Journal of Cleaner Production, 2024)

Surface addition of Ag on PbO2 to enable efficient oxygen evolution reaction in pH-neutral media - Siming Li; Meng Shi; Chunxia Wu; Kaiqi Nie; Zheng Wei; Xiaopeng Jiang; Xinbing Liu; Huili Chen; Xinlong Tian; Daoxiong Wu; Yawei Li (Chemical Engineering Journal, 2024)

Impact of Cross-Limb Stent-Graft Configuration on Hemodynamics in Abdominal Aortic Aneurysm Interventional Therapy - Yanqing Xie; Yating Zhu; Yike Shi; Yawei Zhao; Hongpeng Zhang; Fen Li; Hui Song; Lingfeng Chen; Wei Guo (Cardiovascular Engineering and Technology, 2024)

Elucidating drivers of severe wintertime fine particulate matter pollution episodes in the Yangtze River Delta region of eastern China - Lei Shu; Tijian Wang; Jane Liu; Zhixiong Chen; Hao Wu; Yawei Qu; Mengmeng Li; Min Xie (Science of The Total Environment, 2024)

Boron promoted Fe3+/peracetic acid process for sulfamethazine degradation: Efficiency, role of boron, and identification of the reactive species - Yanhong Zhang; Guangbing Liu; Yuzhu Xue; Lichun Fu; Yawei Qian; Minhui Hou; Xiang Li; Chen Ling; Ying Zhang; Yuwei Pan (Journal of Environmental Sciences, 2024)

New insights into micro-algal astaxanthin's effect on deoxynivalenol-induced spleen lymphocytes pyroptosis in Cyprinus carpio: Involving mitophagy and mtROS-NF-κB-dependent NLRP3 inflammasome - Lei Diao; Wenjie Liu; Yawei Xu; Bin Zhang; Lingnan Meng; Rui Yin; Huijie Chen (Fish & Shellfish Immunology, 2024)

Histopathological, physiological, and multi-omics insights into the hepatotoxicity mechanism of nanopolystyrene and/or diclofenac in Mylopharyngodon piceus - Tiantian Chen; Hewei Jiang; Yaoji He; Yawei Shen; Jiajie Fang; Zequn Huang; Yubang Shen; Xiaowu Chen (Environmental Pollution, 2024)

Application of Hydraulic Sensitivity Indicators in Improving Canal Control Capabilities for Irrigation Systems - Yumiao Fan; Xiaohui Jin; Haorui Chen; Yawei Hu; Zhanyi Gao (Water Resources Management, 2024)

WITHDRAWN: Orbital-paced Oceanic Anoxic Event 2 evolution and astrochronology in the Mentelle Basin (Australia) at southern high latitudes - Kang Xu; Yi Zhong; H. Tsikos; Hongjin Chen; Yawei Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Micro-algal astaxanthin ameliorates polystyrene microplastics-triggered necroptosis and inflammation by mediating mitochondrial Ca2+ homeostasis in carp’s head kidney lymphocytes (Cyprinus carpio L.) - Lei Diao; Meiqi Ding; Hongzhen Sun; Yawei Xu; Rui Yin; Huijie Chen (Fish & Shellfish Immunology, 2023)

Degradation of norfloxacin by sulfur-doped iron-cobalt oxides activated perodisulfate: Synergism between free radicals and singlet oxygen - Luwei Zhai; Fengchun Li; Yuhai He; Xia Chen; Xuan Zhang; Yawei Gu; Chongqing Xu; Guihuan Yan; Xiaojing Feng; Wenqiang Jiang (Chemical Engineering Journal, 2023)

Impacts of exposure to nanopolystyrene and/or chrysene at ambient concentrations on neurotoxicity in Siniperca chuatsi - Tiantian Chen; Hewei Jiang; Yawei Shen; Tingwen Cui; Zonglin Yang; Yufei Liu; Jinliang Zhao; Xiaowu Chen (Chemosphere, 2023)

Research on the risk evaluation of urban wastewater treatment projects based on an improved fuzzy cognitive map - Hongyu Chen; Jingyi Wang; Zongbao Feng; Yang Liu; Wen Xu; Yawei Qin (Sustainable Cities and Society, 2023)

Enhanced nitrate removal by alcohol-involved nitrate photolysis-induced advanced reduction process - Yawei Xie; Shiyi Ni; Shiming Wang; Chenda Wu; Keqi Huang; Dehua Ma; Lujun Chen; Rui Liu; Hongyuan Liu (Chemical Engineering Journal, 2023)

Impact of pyraclostrobin on the growth of Fusarium pseudograminearum and its control efficacy against wheat crown rot in Henan Province, China - Ying Hou; Yawei Chen; Lili Wang; Yiheng Zheng; Shengming Liu; Jianqiang Xu (Journal of Plant Pathology, 2023)

Nrf2 protects against renal fibrosis induced by chronic cadmium exposure in mice - Chengjie Chen; Zhengsheng Zhou; Siqi Yu; Yawei Ma; Gang Wang; Xue Han; Congcong Jiao; Junjun Luan; Zhiyuan Liu; Yuanyuan Xu; Huihui Wang; Qiang Zhang; et al. (Food and Chemical Toxicology, 2023)

Bioleaching performance of vanadium-bearing smelting ash by Acidithiobacillus ferrooxidans for vanadium recovery - Xiaoxiao Guo; Siming Chen; Yawei Han; Chunbo Hao; Xiujuan Feng; Baogang Zhang (Journal of Environmental Management, 2023)

Reinforcing supramolecular hyaluronan hydrogels via kinetically interlocking multiple-units strategy - Ruofan Chen; Yujie Li; Yu Jin; Yawei Sun; Zhiyong Zhao; Yun Xu; Jiang-Fei Xu; Yuanchen Dong; Dongsheng Liu (Carbohydrate Polymers, 2023)

Metabolic and transcriptional responses demonstrating enhanced thermal tolerance in domesticated abalone - Feng Yu; Yawei Shen; Wenzhu Peng; Nan Chen; Yang Gan; Qizhen Xiao; Junyu Liu; Yisha Lu; Weihong Lin; Zhaofang Han; Xuan Luo; Weiwei You; et al. (Science of The Total Environment, 2023)

Valorization of the microalgae fixing CO2 from flue gas by co-hydrothermal liquefaction with high-protein microalgae: Denitrogenation of bio-oil by ash and high energy recovery - Huihui Liu; Youjian Zhu; Wei Yang; Yawei Li; Haiping Yang; Yingquan Chen; Xianhua Wang; Hanping Chen (Fuel, 2023)

Exploring the mechanism of Chaihujia Longgu Muli decoction in the treatment of epilepsy in rats based on the RhoA/ROCK signaling pathway - Gang Feng; Xianghua Liu; Baoying Wang; Ruixing Li; Yaxin Chang; Nannan Guo; Yawei Li; Tiantian Chen; Bingxiang Ma (Molecular Biology Reports, 2023)

What Drives Migrants Back to Set up Firms? Return-home Entrepreneurial Intention of Rural Migrant Workers in China - Huasheng Zhu; Yawei Chen; Hua Zhang; Zhangfei Liu (Chinese Geographical Science, 2023)

Can financial efficiency and environmental regulation promote R&D innovation? From the perspective of value chain decomposition - Wei Chen; Changqi Tao; Wandan Zou; Shufen Chen; Javier Cifuentes-Faura; Yawei Qi (Environmental Science and Pollution Research, 2023)

Innovative calcium-doped layered yttrium hydroxides for rapid and efficient removal of fluoride from aqueous solutions: Insight into adsorption mechanism - Ying Liang; Fengjie Chen; Meng Zhang; Lufeng Chen; Yu Xia; Zhen Zhou; Bolei Chen; Lixia Zhao; Yong Liang; Yawei Wang (Journal of Environmental Chemical Engineering, 2023)

Development of a synthetic transcription factor-based S-adenosylmethionine biosensor in Saccharomyces cerevisiae - Yawei Chen; Huijie Zheng; jiajia Yang; Yiting Cao; Huiyun Zhou (Biotechnology Letters, 2023)

Effects of Different Levels of Organic Trace Minerals on Oxidative Status and Intestinal Function in Weanling Piglets - Shangchu Wang; Shujun Wu; Yawei Zhang; Juan Chen; Xihong Zhou (Biological Trace Element Research, 2023)

Radial and seasonal variation of sap flow and its response to meteorological factors in sandy Pinus sylvestris var. mongolica plantations in the Three North Shelterbelt of China - Yuqiang Tong; Jing Liu; Xu Han; Tong Zhang; Yinghao Dong; Mengge Wu; Shengjin Qin; Yawei Wei; Zhenju Chen; Yongbin Zhou (Agricultural and Forest Meteorology, 2023)

Facile Fabrication of Amino Functionalized Magnetic Multi-walled Carbon Nanotubes for Removal of Congo Red from Aqueous Solutions - Guobin Song; Liya Tong; Shuhua Chen; Jing Zhang; Yi Zhang; Haonan Wang; Yawei Shi; Ya Sun; Guanghui Ding (Water, Air, & Soil Pollution, 2022)

Sestrin2 attenuates renal damage by regulating Hippo pathway in diabetic nephropathy - Yawei Bian; Chonglin Shi; Shan Song; Lin Mu; Ming Wu; Duojun Qiu; Jiajia Dong; Wei Zhang; Chen Yuan; Dongyun Wang; Zihui Zhou; Xuan Dong; et al. (Cell and Tissue Research, 2022)

Twin peaks of in-hospital mortality among patients with STEMI across five phases of COVID-19 outbreak in China: a nation-wide study - Jianping Li; Nan Zhang; Ziyi Zhou; Xiao Huang; Weiyi Fang; Hongbing Yan; Jiyan Chen; Weimin Wang; Dingcheng Xiang; Xi Su; Bo Yu; Yan Wang; et al. (Science China Life Sciences, 2022)

Numerical Investigation on Higher-Order Harmonic Waves Induced by a Submerged Inclined Plate - Zhimin Zhou; Yawei Sun; Lifen Chen; Dezhi Ning; Sulisz Wojciech (Journal of Marine Science and Engineering, 2022)
In this paper, a two-dimensional time-domain numerical flume has been established to model and investigate nonlinear interactions between nonlinear surface waves and a submerged inclined thin plate. The model solves the Laplace equation and the fully nonlinear free surface boundary conditions within the framework of potential flow theory based on the high-order boundary element method. The mixed Euler–Lagrangian method is applied to update the water surface at each time step, and the fourth-order Runge–Kutta method for time stepping. A so-called four-point method was employed to separate the second-order harmonic free and bounded wave that has the same wave frequency but different wave celerity in front of and behind the submerged plate. It is found that the amplitude of the second-order harmonic free wave increases with the inclination angle of the submerged plate, and the level/amount of the increase is larger for a larger wave steepness. In addition, the amplitudes of both the second-order reflected and transmitted waves are found to increase with the wave steepness, and their empirical relationships are derived for potential use in practical engineering.

Design and evaluation of chitosan-amino acid thermosensitive hydrogel - Jianan Tong; Huiyun Zhou; Jingjing Zhou; Yawei Chen; Jing Shi; Jieke Zhang; Xinyu Liang; Tianyuan Du (Marine Life Science & Technology, 2022)

Promoter methylation and expression of the rassf4 gene in Nile tilapia ( Oreochromis niloticus ) - Yawei Shen; Huiyang Li; Min Zhou; Shoujie Tang; Yan Zhao; Jinliang Zhao; Xiaowu Chen (Journal of Fish Biology, 2021)
Oreochromis niloticus RAS‐association domain family 4 ( rassf4 ) was specifically expressed in the ovaries. Immunohistochemistry results showed that Rassf4 was located in follicular cells. The methylation percentages of the promoter region (−734/−1012) of rassf4 in the ovaries and testes were 13.28% and 92.85%, respectively. Deleting the fragment of −734 to −1012 sites significantly reduced the basal activity of the rassf4 promoter to 62.33%, which indicated that this region was important for the transcription of the rassf4 gene. This study lays the foundation for further research on the function of fish rassf4 .

Multiplex genome editing using a dCas9-cytidine deaminase fusion in Streptomyces - Yawei Zhao; Jinzhong Tian; Guosong Zheng; Jun Chen; Chuanwen Sun; Zhongyi Yang; Andrei A. Zimin; Weihong Jiang; Zixin Deng; Zhijun Wang; Yinhua Lu (Science China Life Sciences, 2020)

Expression profile analyses of mettl8 in Oryzias latipes - Wei Pang; Ziwei Zhao; Yawei Shen; Yanhui Bi; Yifeng Gu; Xiaowu Chen (Fish Physiology and Biochemistry, 2020)

Antimicrobial Peptide JH-3 Effectively Kills Salmonella enterica Serovar Typhimurium Strain CVCC541 and Reduces Its Pathogenicity in Mice - Lei Wang; Xueqin Zhao; Xiaojing Xia; Chunling Zhu; Wanhai Qin; Yanzhao Xu; Bolin Hang; Yawei Sun; Shijun Chen; Huihui Zhang; Jinqing Jiang; Jianhe Hu; et al. (Probiotics and Antimicrobial Proteins, 2019)

5-FU preferably induces apoptosis in BRAF V600E colorectal cancer cells via downregulation of Bcl-xL - Tongfei Shi; Mohan Gao; Meihui He; Fengli Yue; Yawei Zhao; Madi Sun; Kan He; Li Chen (Molecular and Cellular Biochemistry, 2019)

Losartan suppresses the inflammatory response in collagen-induced arthritis by inhibiting the MAPK and NF-κB pathways in B and T cells - Xinming Wang; Xiaoyun Chen; Wei Huang; Pengying Zhang; Yawei Guo; Heinrich Körner; Huaxun Wu; Wei Wei (Inflammopharmacology, 2019)

Population susceptibility differences and effects of air pollution on cardiovascular mortality: epidemiological evidence from a time-series study - Mengyao Liu; Xiaoxia Xue; Baosen Zhou; Yawei Zhang; Baijun Sun; Jianping Chen; Xuelian Li (Environmental Science and Pollution Research, 2019)

Irf3 from mandarin fish thymus initiates interferon transcription - Xiaowu Chen; Yawei Shen; Minglin Wu; Jinliang Zhao (Fish Physiology and Biochemistry, 2019)

Influence of Atmospheric Particulate Matter on Ozone in Nanjing, China: Observational Study and Mechanistic Analysis - Yawei Qu; Tijian Wang; Yanfeng Cai; Shekou Wang; Pulong Chen; Shu Li; Mengmeng Li; Cheng Yuan; Jing Wang; Shaocai Xu (Advances in Atmospheric Sciences, 2018)

A parameter-free progressive TIN densification filtering algorithm for lidar point clouds - Xiaotian Shi; Hongchao Ma; Yawei Chen; Liang Zhang; Weiwei Zhou (International Journal of Remote Sensing, 2018)

Design of gas drainage modes based on gas emission rate in a gob: a simulation study - Xiaowei Li; Chaojie Wang; Yujia Chen; Jun Tang; Yawei Li (Arabian Journal of Geosciences, 2018)

Ionizing Radiation Blocks Hair Cell Regeneration in Zebrafish Lateral Line Neuromasts by Preventing Wnt Signaling - Rong Li; Guixiang Liao; Guo Yin; Baiyao Wang; Miaohong Yan; Xiaoshan Lin; Wenqing Zhang; Xiaohui Chen; Shasha Du; Yawei Yuan (Molecular Neurobiology, 2018)

Instantaneous BDS + GPS undifferenced NRTK positioning with dynamic atmospheric constraints - Xuan Zou; Yawei Wang; Chenlong Deng; Weiming Tang; Zongnan Li; Jianhui Cui; Chen Wang; Chuang Shi (GPS Solutions, 2018)

Processes of coastal ecosystem carbon sequestration and approaches for increasing carbon sink - Yao Zhang; MeiXun Zhao; Qiu Cui; Wei Fan; JiaGuo Qi; Ying Chen; YongYu Zhang; KunShan Gao; JingFeng Fan; GuangYi Wang; ChongLing Yan; HaoLiang Lu; et al. (Science China Earth Sciences, 2017)

Spatio-temporal distribution of fecal indicators in three rivers of the Haihe River Basin, China - Yawei Wang; Yanan Chen; Xiang Zheng; Chengmin Gui; Yuansong Wei (Environmental Science and Pollution Research, 2017)

Fouling analysis of membrane bioreactor treating antibiotic production wastewater at different hydraulic retention times - Dawei Yu; Yutao Chen; Yuansong Wei; Jianxing Wang; Yawei Wang; Kun Li (Environmental Science and Pollution Research, 2017)

Metals compositions of indoor PM2.5, health risk assessment, and birth outcomes in Lanzhou, China - Yaqun Zhang; Suzhen Cao; Xiaoying Xu; Jie Qiu; Mingxia Chen; Dennis Wang; Donghong Guan; Chengyuan Wang; Xiao Wang; Bowen Dong; Huang Huang; Nan Zhao; et al. (Environmental Monitoring and Assessment, 2016)

Air Quality in Lanzhou, a Major Industrial City in China: Characteristics of Air Pollution and Review of Existing Evidence from Air Pollution and Health Studies - Yaqun Zhang; Min Li; Mercedes A. Bravo; Lan Jin; Amruta Nori-Sarma; Yanwen Xu; Donghong Guan; Chengyuan Wang; Mingxia Chen; Xiao Wang; Wei Tao; Weitao Qiu; et al. (Water, Air, & Soil Pollution, 2014)

Multilayer Pressure Containment Model and its Application in Deep Well Fractured Formation - Pei Yang; Mian Chen; Yan Jin; Bing Hou; Yunhu Lu; Chuan Liang; Qianqian Zhu; Yawei Li (Rock Mechanics and Rock Engineering, 2013)

Dominantly Inherited Myotonia Congenita Resulting from a Mutation That Increases Open Probability of the Muscle Chloride Channel CLC-1 - David P. Richman; Yawei Yu; Ting-Ting Lee; Pang-Yen Tseng; Wei-Ping Yu; Ricardo A. Maselli; Chih-Yung Tang; Tsung-Yu Chen (NeuroMolecular Medicine, 2012)

A Novel Method for Automatic Identification of Motion Artifact Beats in ECG Recordings - Yuewen Tu; Xiuquan Fu; Dingli Li; Chao Huang; Yawei Tang; Shuming Ye; Hang Chen (Annals of Biomedical Engineering, 2012)

Soil bacterial community composition and diversity respond to cultivation in Karst ecosystems - Xiangbi Chen; Yirong Su; Xunyang He; Yawei Wei; Wenxue Wei; Jinshui Wu (World Journal of Microbiology and Biotechnology, 2012)